Do up-front tax incentives affect private pension saving in the United Kingdom? - Rowena Crawford; Richard Disney; Carl Emmerson (Institute for Fiscal Studies (IFS), 2012)
The paper examines how individuals respond to complex decision-making environments - in particular, whether up-front financial incentives are an effective policy lever to change behaviour. The paper argues that incentives differ in their transparency and in their complexity; individuals are more likely to respond to incentives that are both transparent and imply a large pay-off in terms of net income. The paper focuses on household 'tax planning' in the context of tax reliefs for retirement saving in the United Kingdom. It examines whether take-up of retirement saving instruments increases at the higher rate threshold for income tax, since tax relief is given at the marginal tax rate and should be more attractive to those just above this threshold than to those just below it. It then examines a more complex case where the tax system provides an incentive for pension saving to do be done by one member of a couple. Econometric results are obtained from the Family Resources Survey on these two tests of household responses to complex incentives.
Keywords: E21; H24; 330; Tax incentives; Retirement saving; Regression discontinuity